Apolipoprotein D and transthyretin are reduced in female adolescent offspring of women with type 1 diabetes: The EPICOM study. Issue 7 (28th December 2021) - Overgaard, Martin; Ravnsborg, Tina; Lohse, Zuzana; Bytoft, Birgitte; Clausen, Tine D.; Jensen, Rikke B.; Damm, Peter; Højlund, Kurt; Gravholt, Claus H.; Knorr, Sine; Jensen, Dorte M.
Abstract: Aims: Adolescent offspring exposed to maternal diabetes during intrauterine life show a less favourable metabolic profile than the background population. Here, we hypothesize that offspring of women with type 1 diabetes (T1D), possess sex‐specific alterations in the serum profile of proteins involved in lipid, metabolic and transport processes and that these alterations are associated with lipid profile and indices of insulin sensitivity and secretion. Methods: A prospective nationwide follow‐up study (EPICOM) in a Danish population. Blood samples were assessed from offspring of women with T1D (index offspring, n  = 267, 13–20 years), and matched control offspring ( n  = 290). Serum proteins were analysed using a 25‐plex cardio‐metabolic targeted proteomics assay, which includes 12 apolipoproteins and 13 transport and inflammatory proteins. Results: Apolipoprotein D (ApoD) and transthyretin (TTR) were reduced in index females as compared to female controls (−8.1%, p  < 0.001 and −6.1%, p  = 0.006 respectively), but not in index males (2.2%, p  = 0.476 and −2.4%, p  = 0.731 respectively). Sex‐dependent inverse associations between exposure to maternal T1D in utero and ApoD and TTR were significant after adjusting for age, BMI‐SDS and Tanner stage (OR = 0.252 [95% CI 0.085, 0.745], p  = 0.013 and OR = 0.149 [95% CI 0.040, 0.553], p  = 0.004). ApoD correlated to indices of insulin sensitivity and secretion in a similar sex‐specific pattern in crude and adjusted analyses. Conclusions: Low ApoD may be regarded as an early risk marker of metabolic syndrome. A possible link between ApoD and cardiovascular disease needs further investigation.